2013
DOI: 10.1155/2013/476276
|View full text |Cite
|
Sign up to set email alerts
|

Current Progress and Challenges in the Search for Autism Biomarkers

Abstract: Autism spectrum disorders (ASD) encompass a range of neurodevelopmental conditions that are clinically and etiologically very heterogeneous. ASD is currently diagnosed entirely on behavioral criteria, but intensive research efforts are focused on identifying biological markers for disease risk and early diagnosis. Here, we discuss recent progress toward identifying biological markers for ASD and highlight specific challenges as well as ethical aspects of translating ASD biomarker research into the clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 117 publications
0
33
0
Order By: Relevance
“…Longstanding interest in potential biomarkers for the diagnosis of ASD dates back to studies on blood serotonin reported in the 1970s 56. Several reviews have highlighted the potential benefits of earlier detection and targeted interventions by pursuing assessment measures that focus on underlying biology rather than downstream behavioral effects 1057585960…”
Section: Potential For Presymptomatic Detection: Advances In Biomarkementioning
confidence: 99%
“…Longstanding interest in potential biomarkers for the diagnosis of ASD dates back to studies on blood serotonin reported in the 1970s 56. Several reviews have highlighted the potential benefits of earlier detection and targeted interventions by pursuing assessment measures that focus on underlying biology rather than downstream behavioral effects 1057585960…”
Section: Potential For Presymptomatic Detection: Advances In Biomarkementioning
confidence: 99%
“…Identifying biomarkers for ASDs (Voineagu and Yoo, 2013) has been the focus of intense research since the first description of the disease in the early 1940s (Kanner, 1943). Biomarkers of oxidative stress, as a result of impaired antioxidant mechanism and aberrant neuroimmune responses, have been associated with ASDs (Frustaci et al, 2012;Wei et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…37 Numerous investigations have addressed the potential use of biological indices related to oxidative stress as autism indicators. 7,32 The present study employed ROC analysis to show that autism may be diagnosed with 71.1% sensitivity and 82.6% specificity, at a serum TAS level <1.20.…”
Section: Resultsmentioning
confidence: 99%